2021
DOI: 10.1007/s11356-021-14774-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sex steroid hormones and reproductive irregularities in diethyl phthalate-exposed premature mice: modulatory effect of raw honey against potential anomalies

Abstract: Phthalates, plasticizing chemicals are top-rated environmental contaminants. Diethyl phthalate (DEP), a chief member of this family was declared a potent endocrine-disruptor and carcinogen in animals and humans. The current study was designed to explore the probable reproductive damage induced by DEP and the therapeutic e cacy of raw honey in male albino mice. Four weeks old 50 male mice, were randomized equally in ve groups, as control (C) received 0.1 ml distilled water; vehicle control (VC) received 0.1 ml … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…The NS floral honey and NS oil treated groups rebalance the TT to be near the value of the negative control group. These findings are in line with recent studies by many researchers [ 3 , 12 , 38 ]. Mice given black seed oil had considerably higher serum TT concentrations [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The NS floral honey and NS oil treated groups rebalance the TT to be near the value of the negative control group. These findings are in line with recent studies by many researchers [ 3 , 12 , 38 ]. Mice given black seed oil had considerably higher serum TT concentrations [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, honey from two sources (M-floral honey and NS floral honey) did not influence sperm quality, and this finding agrees with the work of Dare et al [ 74 ] [2013], who reported reduced motility and an increased percentage of dead and abnormal spermatozoa in honey-treated animals. Contrarily, the concomitant use of honey with toxic diethyl phthalate exposure has shown a significant improvement in healthy sperm count [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations